A Novel Liver-Specific Pseudogene Biomarker, BMS1P8, for Diagnosis and Prognosis in Hepatocellular Carcinoma - Hyung Seok Kim; Ji Yi Choi; Geum Ok Baek; Moon Gyeong Yoon; Se Ha Jang; Ji Eun Han; Soon Sun Kim; Jae Youn Cheong; Jee-Yeong Jeong; Jung Woo Eun (Frontiers in Bioscience-Landmark)
Background: Hepatocellular carcinoma (HCC) is the leading cause of cancer-related mortality worldwide. Despite advances in therapeutic approaches, the lack of effective biomarkers continues to limit early detection and prognostic evaluation. Pseudogenes, once considered nonfunctional, have emerged as regulators of biological processes in tumors and as potential biomarkers. This study aimed to identify and validate BMS1 Pseudogene 8 (BMS1P8) as a liver-specific, clinically relevant diagnostic and prognostic biomarker in HCC. Methods: A comprehensive survey of pseudogene expression across different stages of liver disease was performed and validated using clinical HCC samples. Correlation, enrichment, and competing endogenous RNA (ceRNA) analyses integrating matched microRNA (miRNA)-seq and mRNA-seq were used to explore the functional networks surrounding BMS1P8. Public RNA-seq datasets (GSE114564, The Cancer Genome Atlas-Liver Hepatocellular Carcinoma (TCGA_LIHC)) were used to delineate differentially expressed pseudogenes, and 98 paired tumor and non-tumor tissues were assessed using quantitative reverse transcription polymerase chain reaction. Diagnostic and prognostic performances were evaluated using receiver operating characteristic curves and Kaplan–Meier statistics. Results: BMS1P8 was markedly upregulated in HCC and was overexpressed in 25 other cancer types. Receiver operating characteristics analysis yielded an area under the curve of 0.81, underscoring the diagnostic utility. High BMS1P8 expression and enrichment of cell cycle pathways were associated with poor survival. ceRNA screening revealed an inverse BMS1P8–miR-30c-2-3p correlation and concordant NME/NM23 nucleoside diphosphate kinase 6 (NME6) upregulation, with the BMS1P8/miR-30c-2-3p/NME6 triad further stratifying patient outcomes. Conclusion: Our findings highlight BMS1P8 as a novel liver-specific biomarker with substantial diagnostic and prognostic value in HCC. Its diagnostic utility suggests its potential application in early detection and personalized treatment strategies, contributing to improved patient outcomes.